Silicon-carbon composite, its manufacturing method, and anode active material and lithium secondary battery containing the same

The silicon-carbon composite, with a controlled oxygen-to-silicon molar ratio and a carbon layer formed through chemical pyrolysis deposition, addresses the volume expansion issues in silicon-based negative electrode active materials, enhancing the performance of lithium secondary batteries in terms of discharge capacity, initial efficiency, and capacity retention.

JP2025508744APending Publication Date: 2025-04-10DAEJOO ELECTRONICS MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024548625
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-17
Filing Date
2023-02-17
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing silicon-based negative electrode active materials for lithium secondary batteries face challenges such as significant volume expansion (up to 300%) during lithium intercalation, leading to electrode degradation and reduced cycle characteristics.

Method used

A silicon-carbon composite is developed, comprising silicon particles and carbon, with a controlled molar ratio of oxygen to silicon atoms ranging from 0.01 to 0.45. This composite is prepared through a method involving etching of silicon-based raw materials, followed by filtering, drying, and chemical pyrolysis deposition to form a carbon layer.

Benefits of technology

The silicon-carbon composite significantly improves the discharge capacity, initial efficiency, and capacity retention rate of lithium secondary batteries by mitigating volume expansion and enhancing mechanical properties and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025508744000001_ABST
    Figure 2025508744000001_ABST
Patent Text Reader

Abstract

The present invention relates to a silicon-carbon composite, a method for producing the same, and an anode active material containing the same. The silicon-carbon composite is a silicon-carbon composite containing silicon particles and carbon. Since the molar ratio of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite satisfies 0.05 to 0.45, when the silicon-carbon composite is used as an anode active material, it is possible to simultaneously improve the discharge capacity, initial efficiency, and capacity retention rate after cycling of a lithium secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silicon-carbon composite, a method for preparing the same, and a negative electrode active material and a lithium secondary battery containing the same. [Background technology]

[0002] In recent years, with the development of the information and communications industry, electronic devices have become smaller, lighter, thinner, and more portable, and this has led to an increased demand for higher energy density batteries used as power sources for these devices. Lithium secondary batteries are the batteries that can best meet this demand, and research into small batteries using these batteries is being actively conducted, along with their application to large electronic devices such as automobiles and power storage systems.

[0003] Carbon materials are widely used as the negative electrode active material in such lithium secondary batteries. Silicon-based negative electrode active materials are being researched to further improve the capacity of batteries. The theoretical capacity of silicon (4,199 mAh / g) is more than 10 times greater than that of graphite (372 mAh / g), so a significant improvement in battery capacity is expected.

[0004] The reaction scheme when lithium is intercalated into silicon is, for example, as follows: [Reaction Scheme 1] 22Li+5Si=Li 22 Si5

[0005] In silicon-based negative electrode active materials according to the above reaction scheme, high capacity alloys containing up to 4.4 lithium atoms per silicon atom are formed. However, in most silicon-based negative electrode active materials, the intercalation of lithium causes a volume expansion of up to 300%, which destroys the negative electrode and makes it difficult to exhibit high cycle characteristics.

[0006] This volume change may also cause cracks on the surface of the negative electrode active material, and the formation of ionic materials inside the negative electrode active material may cause the negative electrode active material to be electrically separated from the current collector, which may significantly reduce the capacity retention rate of the battery.

[0007] To solve this problem, Japanese Patent No. 4393610 discloses an anode active material in which silicon and carbon are mechanically processed to form a composite, and the surfaces of the silicon particles are coated with a carbon layer by chemical vapor deposition (CVD). In addition, Japanese Patent Publication No. 2016-502253 discloses an anode active material containing silicon-based particles and carbon particles, in which the carbon particles contain fine carbon particles and coarse carbon particles having different average particle sizes.

[0008] However, although these prior art documents relate to negative electrode active materials containing silicon and carbon, there is a limit to suppressing the volume expansion and contraction during charging and discharging. Therefore, research to solve these problems is still required. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 4393610 [Patent Document 2] Special Publication No. 2016-502253 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made to solve the above problems of the prior art. The purpose of the present invention is to provide a silicon-carbon composite that contains silicon particles and carbon, and has a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite that satisfies a specific range, thereby having an excellent capacity retention rate as well as significantly improved discharge capacity and initial efficiency when used as a negative electrode active material.

[0011] It is another object of the present invention to provide silicon-carbon composites of various structures having a core-shell structure.

[0012] Another object of the present invention is to provide a method for preparing said silicon-carbon composite.

[0013] Another object of the present invention is to provide a negative electrode active material containing the above silicon-carbon composite and a lithium secondary battery containing the same. [Means for solving the problem]

[0014] In order to achieve the above object, the present invention provides a silicon-carbon composite comprising silicon particles and carbon, in which the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite is 0.01 to 0.45.

[0015] The present invention also provides a method for preparing a silicon-carbon composite, comprising: a first step of etching a silicon-based raw material powder with an etching solution containing a fluorine (F) atom-containing compound; a second step of filtering and drying a product obtained by the etching to prepare a silicon composite; and a third step of coating the inside of the silicon composite with carbon, or coating the inside of the silicon composite with carbon and forming a carbon layer on the surface thereof, using a chemical pyrolysis deposition method to obtain a silicon-carbon composite.

[0016] The present invention also provides a negative electrode active material comprising the silicon-carbon composite.

[0017] The present invention further provides a lithium secondary battery comprising the negative electrode active material. Effect of the Invention

[0018] According to an embodiment, the silicon-carbon composite contains silicon particles and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite satisfies a specific range, so that when this is used together with a binder and a conductive material as the negative electrode active material of a lithium secondary battery to prepare a negative electrode active material composition, this is easily dispersible and has excellent mechanical properties such as strength, and can improve the performance of the lithium secondary battery. Furthermore, by controlling the porosity of the silicon-carbon composite, the discharge capacity, initial efficiency, and capacity retention rate of the lithium secondary battery can be further improved.

[0019] According to another embodiment, the silicon-carbon composite has a core-shell structure, the core comprises silicon particles and carbon, and the shell comprises at least one or more carbon layers. This further increases the strength of the shell layer, and increases the bond (adhesion) between the silicon-carbon composite and the binder, which can reduce the electrode expansion rate. As a result, it is possible to simultaneously improve the discharge capacity, initial efficiency and capacity retention rate of the lithium secondary battery.

[0020] Additionally, the preparation method according to an embodiment has the advantage that it allows for mass production by a continuous process with minimal steps. [Brief description of the drawings]

[0021] The following drawings attached to this specification illustrate preferred embodiments of the present invention, and together with the description of the present invention, are useful for further understanding of the technical concept of the present invention. Therefore, the present invention should not be construed as being limited only to those depicted in the drawings. [Figure 1] FIG. 1 is a schematic diagram illustrating a process for preparing a silicon-carbon composite according to an embodiment. [Diagram 2] 1 is a photograph at a magnification of 30,000 times showing the silicon composite (B1) prepared in Example 1 analyzed by an ion beam scanning electron microscope (FIB-SEM). [Diagram 3]1 is a photograph at a magnification of 30,000 times of the silicon-carbon composite prepared in Example 1 analyzed by an ion beam scanning electron microscope (FIB-SEM). [Figure 4] 1 is an ion beam transmission electron microscope (TEM-FIB) photograph of the silicon-carbon composite prepared in Example 1. [Diagram 5] FIG. 2 is a diagram showing the results of X-ray diffraction analysis of the silicon-carbon composite prepared in Example 1. [Figure 6] FIG. 2 shows the results of Raman spectroscopic analysis of the silicon-carbon composite prepared in Example 1. [Figure 7] FIG. 1 shows the results of X-ray diffraction analysis of the silicon-carbon composite prepared in Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention is not limited to the following disclosure, but may be modified in various ways without departing from the spirit and scope of the present invention.

[0023] In the drawings accompanying this specification, some components are exaggerated, omitted, or depicted diagrammatically, and the size of each component does not completely reflect the actual size.

[0024] Like reference numbers refer to like elements throughout this specification.

[0025] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The singular terms "a," "an," and "the" include the plural terms unless the context clearly dictates otherwise.

[0026] In this specification, when a component is described as being formed above or below another component, it means that one component is formed above or below the other component, either directly, or indirectly through the other component.

[0027] In this specification, when a part is referred to as "comprising" an element, it should be understood that the part may also include other elements, unless otherwise indicated.

[0028] Also, all numbers and expressions relating to quantities of ingredients, reaction conditions, and the like used herein should be understood to be modified by the term "about" unless otherwise indicated.

[0029] [Silicon-carbon composite] A silicon-carbon composite according to one embodiment includes silicon particles and carbon, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite is 0.01 to 0.45.

[0030] The silicon-carbon composite according to an embodiment contains silicon particles and carbon, so that it is possible to ensure sufficient electrical conductivity of the silicon-carbon composite and to appropriately adjust the specific surface area. Therefore, when this is used as the negative electrode active material of a lithium secondary battery, the performance of the lithium secondary battery can be further improved. Furthermore, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite satisfies a specific range, so that it is possible to significantly improve the discharge capacity and initial efficiency while maintaining an excellent capacity retention rate.

[0031] Specifically, according to an embodiment, it is possible to remove most of the silicon dioxide contained in the silicon-carbon composite by etching. In such a case, the surface of the silicon particle may contain a very high fraction of silicon (Si) atoms compared to oxygen (O) atoms. That is, the molar ratio O / Si may be significantly reduced. By using the silicon-carbon composite as the negative electrode active material, a lithium secondary battery having an excellent discharge capacity can be suitably obtained, and at the same time, the initial efficiency of the lithium secondary battery can be improved.

[0032] The molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite can be 0.01 to 0.45, preferably 0.06 to 0.45, more preferably 0.05 to 0.35, and most preferably 0.06 to 0.25.

[0033] If the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite is equal to or greater than the lower limit of the above range, the expansion and contraction caused by charging and discharging the lithium secondary battery can be suppressed. Therefore, when the silicon-carbon composite is used as a negative electrode active material, it is possible to suppress the peeling of the negative electrode active material from the negative electrode current collector. In addition, if the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms is equal to or less than the upper limit of the above range, a sufficient discharge capacity can be secured, and therefore high charge and discharge characteristics can be maintained.

[0034] The structure of a silicon-carbon composite according to an embodiment will be described in detail below.

[0035] <Structure of silicon-carbon composite> A silicon-carbon composite according to some embodiments includes silicon particles and carbon.

[0036] Figure 1 is a schematic diagram illustrating a process for preparing a silicon-carbon composite according to an embodiment. Figure 1(C) and Figure 1(D) are simplified schematic diagrams of cross-sections of the structure of a silicon-carbon composite according to various embodiments of the present invention. Figure 1(B) and its preparation process will be described in detail in the method for preparing a silicon-carbon composite described below.

[0037] First, referring to Figures 1(C) and 1(D), a silicon-carbon composite includes silicon particles (20) and carbon (45).

[0038] The silicon-carbon composite may include silicon particles (20), specifically silicon agglomerates in which the silicon particles (20) are joined (or interconnected) to one another. The carbon layer (40) may be formed on the surface of the silicon particles and / or silicon agglomerates. Also, the carbon (45) may be formed such that it is uniformly dispersed and / or distributed among the silicon particles (20).

[0039] As used herein, the term "coalesced (or interconnected) with" refers to a state in which silicon particles in a silicon-carbon composite are coalesced (fused) with at least one other silicon particle and connected to each other, or to a structure in which silicon particles are continuously connected (silicon agglomerates).

[0040] The interior of the silicon-carbon composite can be more firmly bound by the carbon (45) and the carbon layer (40), thereby minimizing crushing of the silicon-carbon composite that may be caused by volume changes during charging and discharging of the lithium secondary battery.

[0041] The silicon-carbon composite is a composite in which silicon agglomerates, in which multiple silicon particles (20) are joined together, are uniformly distributed in the composite having a structure in the form of a mass, for example, in the form of a polyhedron, sphere, or similar shape. This can be in the form of a single composite in which carbon (45) and the carbon-containing carbon layer (40) surround part or all of the surface of one or more silicon particles or part or all of the surface of secondary silicon particles (silicon agglomerates) formed by the aggregation of two or more silicon particles.

[0042] That is, a large amount of carbon (45) is formed inside the silicon-carbon composite, and the carbon layer (40) containing carbon is uniformly formed so as to surround the silicon particles (20). This has the advantage that it is possible to ensure high electrical conductivity and to reduce the amount of carbon-based negative electrode active material added when manufacturing the negative electrode. In addition, the specific surface area of ​​the silicon-carbon composite is appropriately adjusted so as to further improve the performance of the lithium secondary battery.

[0043] The silicon-carbon composite may also contain pores (10).

[0044] When the silicon-carbon composite contains pores (10), the volumetric expansion of the silicon particles (20) that may occur during charging and discharging of a lithium secondary battery can be absorbed by the pores, thereby effectively mitigating and suppressing problems caused by the volumetric expansion.

[0045] On the other hand, according to some embodiments, the silicon-carbon composite may have a core-shell structure.

[0046] Specifically, the silicon-carbon composite may have a core-shell structure, where the core may include silicon particles and carbon, and the shell may include a carbon layer.

[0047] Silicon-carbon composites according to embodiments including a core-shell structure may include a shell that includes a carbon layer (carbon film) on the surface of the core.

[0048] In the silicon-carbon composite, the carbon layer forming the shell can be formed or laminated in various ways as long as the desired effect is not impaired. The shell can include up to 4 layers, specifically 1 to 4 layers, preferably 1 to 3 layers, for example 1 or 2 layers of carbon.

[0049] For example, according to one embodiment, a silicon-carbon composite (hereinafter referred to as “silicon-carbon composite (1)”) can be provided that has a core-shell structure, with the shell having a single-layer structure composed of a first carbon layer.

[0050] Specifically, referring to Figure 1(C), the silicon-carbon composite (1) may have a core-shell structure, where the core may include silicon particles (20) and carbon (45) and the shell may include a first carbon layer (40). Also, the silicon-carbon composite (1) may include pores (10) therein.

[0051] The silicon-carbon composite (1) contains a carbon layer having a monolayer structure on the surface of the core, which enhances the strength of the core. It also ensures excellent electrical conductivity even after the electrode expands during charging and discharging. In addition, side reactions with the electrolyte are suppressed, which makes it possible to improve the charge-discharge capacity, initial charge-discharge efficiency, and capacity retention rate of the secondary battery.

[0052] According to another embodiment, there may be provided a silicon-carbon composite (hereinafter referred to as “silicon-carbon composite (2)”) having a core-shell structure, in which the shell has a multilayer structure including at least two carbon layers including a first carbon layer and a second carbon layer.

[0053] That is, the shell may have a multi-layer structure including at least two carbon layers, including a first carbon layer and a second carbon layer.

[0054] Specifically, referring to Figure 1 (D), the silicon-carbon composite (2) may have a core-shell structure, where the core may include silicon particles (20) and carbon (45), and the shell may include a first carbon layer (40) and a second carbon layer (50) formed on the first carbon layer (40). The silicon-carbon composite (2) may also include pores (10) therein.

[0055] When the shell is composed of at least two carbon layers, even if a crack forms on the surface of one of the carbon layers, the carbon layers can remain electrically connected until the other, crack-free, carbon layer is completely separated.

[0056] The first carbon layer may be present on a surface of the core, and the first carbon layer may be present on a surface of the silicon particles and / or silicon agglomerates.

[0057] In addition, the shell has a structure surrounding the core, and at least one carbon layer employed therein, i.e., a first carbon layer, or at least two carbon layers including a first carbon layer and a second carbon layer, can provide an effect as a buffer layer (cushion layer).

[0058] The buffer layer is effective as a mechanical buffer support surrounding the core, and more specifically, the buffer layer can suppress core degradation, crack formation, and volume expansion caused by mechanical expansion of silicon during charging and discharging.

[0059] The specific properties of silicon-carbon composites (1) and (2) are described in more detail below in the various examples of silicon-carbon composites.

[0060] <Physical properties of silicon-carbon composites> Silicon-carbon composites have an average particle size (D 50 ).

[0061] In addition, the average particle size of the silicon-carbon composite (D 50 ) is the diameter average particle size (D) at which the cumulative volume reaches 50% in particle size distribution measurement by the laser beam diffraction method. 50 ), i.e., the average particle size or median diameter. The average particle size of silicon-carbon composites (D 50 If the average particle diameter (D) of the silicon-carbon composite is smaller than the above range, there is a concern that the dispersibility of the silicon-carbon composite may decrease due to aggregation of the silicon-carbon composite particles during preparation of the negative electrode slurry (i.e., the negative electrode active material composition) using the silicon-carbon composite. 50 If the specific surface area exceeds the above range, the silicon-carbon composite particles will expand significantly due to the incorporation of lithium ions, and the bonding ability between the silicon-carbon composite particles and between the particles and the current collector will decrease with repeated charging and discharging, which may significantly reduce the life characteristics. In addition, there is a concern that the activity will decrease due to the reduction in the specific surface area.

[0062] Specifically, the average particle size of the silicon-carbon composite (D 50 ) may be preferably 3 μm to 10 μm, more preferably 3 μm to 8 μm. More specifically, the average particle size (D 50 In light of the significant improvement effect of optimizing the average particle size (D 50 ) may be 3 μm to 6 μm.

[0063] The silicon-carbon composite may have a core-shell structure, and the core may have an average particle size of 2 μm to 10 μm, preferably 2 μm to 8 μm, and more preferably 2 μm to 6 μm.

[0064] Silicon-carbon composite is 2m 2 / g~50m 2 / g, preferably 2m 2 / g~40m 2 / g, more preferably 2m 2 / g~20m 2 / g specific surface area (Brunauer-Emmett-Teller method; BET). If the specific surface area of ​​the silicon-carbon composite is smaller than the above range, the charge-discharge characteristics of the lithium secondary battery may be deteriorated. If the specific surface area exceeds the above range, it may be difficult to prepare a negative electrode active material slurry suitable for application to the negative electrode current collector of the lithium secondary battery, the contact area with the electrolyte may increase, the decomposition reaction of the electrolyte may be accelerated, or a side reaction of the lithium secondary battery may be caused.

[0065] Silicon-carbon composites have a density of 1.8 g / cm 3 ~2.5g / cm 3 , preferably 2.0 g / cm 3 ~2.5g / cm 3 , more preferably 2.0 g / cm 3 ~2.4g / cm 3 The density may vary depending on the amount of the carbon layer. In addition, the initial efficiency or cycle life characteristics may be improved by improving the strength of the matrix of the negative electrode active material. In such a case, the density may refer to the true density.

[0066] If the density of the silicon-carbon composite is equal to or higher than the lower limit of the above range, it is possible to suppress cracks in the negative electrode active material powder due to the expansion and contraction of the volume of the negative electrode active material powder during charging and discharging, thereby suppressing cycle deterioration. If the density is equal to or lower than the upper limit of the above range, the impregnation of the electrolyte is improved, which improves the initial charge and discharge capacity.

[0067] When the silicon-carbon composite is used as a negative electrode active material in an electrode (negative electrode), the electrode expansion rate after one charge / discharge cycle can be 55% to 150%, preferably 55% to 100%, and more preferably 60% to 80%, based on the thickness of the electrode.

[0068] The electrode expansion rate may be a value calculated as a percentage of the ratio between the thickness (N1) of a rolled negative electrode before the electrode is manufactured and the thickness (N2) of the negative electrode at 80% of the cycle life measured during evaluation of a secondary battery manufactured using the negative electrode.

[0069] [Formula A] Electrode expansion rate (%) = thickness of negative electrode when measurement is completed at 80% of cycle life (N2) / thickness of rolled negative electrode before electrode production (N1) × 100

[0070] In addition, in the case of a silicon-carbon composite, a silicon-carbon composite (1) having a single-layer structure in which the shell is composed of a first carbon layer and a silicon-carbon composite (2) having a multilayer structure in which the shell includes at least two carbon layers including a first carbon layer and a second carbon layer can have the same or similar properties.

[0071] Each component of the silicon-carbon composite is described in detail below.

[0072] Silicon Particles A silicon-carbon composite according to some embodiments comprises silicon particles.

[0073] The silicon-carbon composite may also include silicon agglomerates in which silicon particles are joined together. Specifically, the silicon-carbon composite may include silicon agglomerates having a three-dimensional (3D) structure in which two or more silicon particles are joined together.

[0074] Since the silicon particles charge the lithium, the capacity of the lithium secondary battery may be reduced without the use of silicon particles. The silicon particles may be crystalline or amorphous, and in particular may be amorphous or a phase similar thereto.

[0075] When the silicon particles are crystalline, the size of the crystallites is small, so that a dense composite can be obtained, which strengthens the strength of the matrix and prevents cracks. Thus, the initial efficiency or cycle life characteristics of the lithium secondary battery can be further improved. Also, when the silicon particles are amorphous or in a phase similar thereto, the expansion or contraction during charging and discharging of the lithium secondary battery is small, so that the battery performance such as capacity characteristics can be further improved.

[0076] Silicon particles have high initial efficiency and battery capacity, but undergo very complex crystal changes as they electrochemically absorb, store and release lithium atoms.

[0077] The silicon particles may be uniformly distributed within the silicon-carbon composite, and in such a case, superior mechanical properties, such as strength, may be achieved.

[0078] Furthermore, the silicon-carbon composite may have a structure in which silicon particles and carbon are uniformly dispersed.

[0079] In addition, the silicon particles and / or silicon aggregates in which silicon particles are bonded to one another in the silicon-carbon composite are preferably uniformly distributed within the silicon-carbon composite.

[0080] In addition, the silicon aggregates as the active material may be uniformly distributed inside the silicon-carbon composite, and may contain silicon particles that are not combined with each other. The silicon particles and / or silicon aggregates may be uniformly distributed inside the silicon-carbon composite. In such a case, excellent electrochemical properties such as charge and discharge may be achieved.

[0081] The silicon particles contained in the silicon-carbon composite according to one embodiment can be of amorphous type, crystalline type having a crystallite size of 2 nm to 10 nm, or a mixture thereof.

[0082] Specifically, when the silicon-carbon composite is subjected to X-ray diffraction (Cu-Kα) analysis using copper as a cathode target and calculated using the Scherrer formula based on the full width at half maximum (FWHM) of the Si(220) diffraction peak at about 2θ=47.5°, the silicon particles can have a crystallite size of 2 nm to 10 nm, preferably 2 nm to 8 nm, and more preferably 2 nm to 5 nm.

[0083] When silicon particles contain crystalline form and the crystallite size of silicon particles is less than 2 nm, it is not easy to prepare them, and the yield after etching may be low.In addition, when the crystallite size of silicon particles exceeds the above range, micropores cannot sufficiently suppress the volume expansion of silicon particles that occurs during charging and discharging, and there will be areas that do not contribute to discharging, and the reduction of Coulomb efficiency, which represents the ratio of charging capacity to discharging capacity, cannot be suppressed.

[0084] The silicon (Si) content in the silicon-carbon composite can be 38% by weight to 80% by weight, preferably 40% by weight to 80% by weight, more preferably 50% by weight to 80% by weight, and even more preferably 50% by weight to 70% by weight, based on the total weight of the silicon-carbon composite.

[0085] If the content of silicon (Si) is less than the above range, the amount of active material for absorbing and releasing lithium is reduced, which may reduce the charge / discharge capacity of the lithium secondary battery. On the other hand, if the content of silicon (Si) exceeds the above range, the charge / discharge capacity of the lithium secondary battery may increase, but on the other hand, the expansion and contraction of the electrode during charging and discharging becomes excessively large, and the negative electrode active material powder is further pulverized, which may deteriorate the cycle characteristics.

[0086] Silicon oxide compounds According to some embodiments, the silicon-carbon composite may further comprise a silicon oxide compound.

[0087] In the present invention, silicon oxide compounds are a general term for amorphous silicon compounds obtained by oxidation of metallic silicon, reduction of silicon dioxide, or by cooling and precipitation of silicon monoxide formed by heating a mixture of silicon dioxide and metallic silicon. This has the formula SiO x In the above formula, x may be 0.4≦x≦2, preferably 0.4≦x<1.5, and more preferably 0.4≦x<1.2.

[0088] Also, low-grade silicon oxide powder, i.e., SiO 2 , where x is 0.4≦x≦1.2. x When the powder is used, lithium silicate is uniformly formed in the silicon-carbon composite, which reduces the volume expansion, and as a result, the cycle characteristics of the lithium secondary battery can be improved.

[0089] Formula SiO x In the formula, if the value of x is smaller than the above range, the lithium secondary battery may expand and contract significantly during charging and discharging, resulting in a deterioration in life characteristics, whereas if the value of x is larger than the above range, the amount of inactive oxide increases, resulting in a decrease in the initial efficiency of the lithium secondary battery.

[0090] In addition, the silicon-carbon composite is a composite of silicon oxide (SiO x , 0.4≦x≦2).

[0091] On the other hand, the content of oxygen (O) in the silicon-carbon composite may be 0.5% by weight to 10% by weight, preferably 0.5% by weight to 8% by weight, more preferably 0.5% by weight to 6% by weight, based on the total weight of the silicon-carbon composite. If the content of oxygen (O) in the silicon-carbon composite is less than the above range, the degree of expansion during charging of the lithium secondary battery may increase. If the content of oxygen (O) in the silicon-carbon composite exceeds the above range, the irreversible reaction with lithium increases, which may reduce the initial charge-discharge efficiency of the lithium secondary battery, the negative electrode active material may easily peel off from the negative electrode current collector, and the charge-discharge cycle may deteriorate.

[0092] On the other hand, generally, as the ratio of oxygen in the negative electrode active material containing silicon decreases, the ratio of silicon particles as active material increases, which increases the discharge capacity and discharge efficiency, but on the other hand, problems may occur in that cracks may be formed in the silicon-carbon composite due to the volume expansion caused by the charge and discharge of silicon particles.As a result, the cycle characteristics of the lithium secondary battery may be reduced.To solve this problem, silicon dioxide may be included in the silicon-carbon composite as an inactive material or inactive phase.

[0093] Specifically, silicon dioxide is an inert material or phase, and is therefore effective in reducing the volume expansion of silicon particles caused by charging and discharging. Silicon dioxide is a component for forming a matrix in silicon-carbon composites, which is effective in increasing the mechanical strength of the matrix of silicon-carbon composites, making it more robust, and suppressing the formation of cracks even during volume expansion.

[0094] Furthermore, when the content of silicon dioxide is optimized, it is possible to suppress the decrease in the initial capacity and initial efficiency of the lithium secondary battery, and to improve the cycle characteristics by increasing the strength of the matrix.

[0095] Specifically, according to an embodiment, the silicon-carbon composite may contain silicon dioxide in an amount of 0.3% to 6% by weight, preferably 0.3% to 5% by weight, more preferably 0.5% to 5% by weight, and most preferably 1% to 4% by weight, based on the total weight of the silicon-carbon composite. If the content of silicon dioxide is less than the above range, the effect of improving the cycle characteristics of the lithium secondary battery may be small. If the content exceeds the above range, it becomes difficult to achieve the desired molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite, and the cycle characteristics or discharge capacity of the lithium secondary battery may decrease.

[0096] carbon The silicon-carbon composite according to some embodiments comprises carbon.

[0097] According to an embodiment, when the silicon-carbon composite contains carbon, it is possible to ensure sufficient electrical conductivity of the silicon-carbon composite and to appropriately adjust the specific surface area, and therefore, when this is used as a negative electrode active material of a lithium secondary battery, it is possible to improve the life characteristics and capacity of the lithium secondary battery.

[0098] In general, the electrical conductivity of the negative electrode active material is an important factor for promoting electron transfer during electrochemical reactions. If the composite as the negative electrode active material does not contain carbon, the electrical conductivity will not reach an appropriate level.

[0099] In silicon-carbon composites, carbon may be present on the surface of the silicon particles contained in the silicon-carbon composite, or carbon may be present on the surface or within the silicon aggregates contained in the silicon-carbon composite.

[0100] Alternatively, carbon may act as a matrix, with silicon particles and pores dispersed in the composite matrix.

[0101] Specifically, the silicon-carbon composite may have an island-in-a-sea structure, with silicon particles or closed pores (v) forming islands and carbon forming a sea. The pores may be open and closed. The closed pores may include pores that are not internally coated with carbon.

[0102] The state in which silicon particles or carbon are uniformly dispersed can be confirmed by observing a dark-field image or a bright-field image using a transmission electron microscope (TEM).

[0103] According to an embodiment, the silicon-carbon composite comprises a silicon composite and a carbon layer on a surface thereof. Specifically, the silicon-carbon composite may comprise a silicon composite comprising silicon particles, and the silicon-carbon composite may comprise a carbon layer on a surface thereof comprising carbon.

[0104] In particular, when the silicon-carbon composite contains a carbon layer, it is possible to improve the electrical contact between particles and provide excellent electrical conductivity even after the electrode expands during charging and discharging, thereby further improving the performance of lithium secondary batteries.

[0105] Also, according to an embodiment, the thickness of the carbon layer or the amount of carbon can be controlled so as to achieve appropriate electrical conductivity while preventing deterioration of life characteristics, thereby making it possible to obtain a high-capacity negative electrode active material.

[0106] The carbon (C) content may be 18% to 60% by weight based on the total weight of the silicon-carbon composite. Specifically, the carbon (C) content may be preferably 20% to 55% by weight, 20% to 50% by weight, or 25% to 45% by weight based on the total weight of the silicon-carbon composite.

[0107] Specifically, when the silicon-carbon composite has a core-shell structure, the carbon (C) content can be the sum of the carbon (C) content in the core and the amount of carbon (C) in the carbon layer contained in the shell.

[0108] If the carbon (C) content is less than the above range, the effect of improving the conductivity cannot be expected sufficiently, and the electrode life of the lithium secondary battery may be deteriorated. Also, if the carbon (C) content exceeds the above range, the discharge capacity of the lithium secondary battery may decrease, and the bulk density may decrease, resulting in a decrease in the charge / discharge capacity per unit volume.

[0109] Furthermore, the silicon-carbon composite contains carbon inside the core, and the carbon (C) content inside the core of the silicon-carbon composite can be 16 wt% to 45 wt%, preferably 18 wt% to 40 wt%, and more preferably 20 wt% to 40 wt%, based on the total weight of the silicon-carbon composite.

[0110] When the content of carbon (C) in the core of the silicon-carbon composite satisfies the above range, sufficient electrical conductivity can be obtained, and the electrical conductivity can be further improved, resulting in a secondary battery having excellent charge / discharge capacity and cycle characteristics.

[0111] The amount of carbon (C) in the carbon layer contained in the shell can be 2 wt % to 10 wt %, preferably 2 wt % to 8 wt %, and more preferably 3 wt % to 6 wt %, based on the total weight of the silicon-carbon composite.

[0112] According to an embodiment, the carbon in the core may include at least one selected from the group consisting of amorphous carbon, crystalline carbon, carbon nanofiber, chemical vapor deposition graphene, reduced graphene oxide, and carbon nanotube, for example, amorphous carbon. In this case, the interface resistance between the silicon particles and the carbon layer on the core surface is reduced, and the intercalation and desorption of lithium is smoothly achieved, thereby ensuring the high output characteristics of the lithium secondary battery.

[0113] In addition, the amorphous carbon inside the core acts as a support for fixing the silicon particles, suppresses the volume change of the silicon particles during charging and discharging, and effectively blocks contact between the silicon particles and the electrolyte.

[0114] The shell may also include a carbon layer (first carbon layer) including at least one selected from the group consisting of amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor deposited graphene, reduced graphene oxide, and carbon nanotubes.

[0115] On the other hand, the thickness of the carbon layer may be 2 nm to 100 nm, preferably 2 nm to 80 nm, and more preferably 3 nm to 50 nm. When the thickness of the carbon layer is equal to or greater than the lower limit of the above range, the electrical conductivity can be improved. When the thickness is equal to or less than the upper limit of the above range, the decrease in the capacity of the lithium secondary battery can be suppressed.

[0116] The average thickness of the carbon layer can be measured, for example, by the following procedure.

[0117] First, the negative electrode active material is observed at an arbitrary magnification using a transmission electron microscope (TEM).

[0118] The magnification is preferably such that it can be seen with the naked eye, for example. Then, the thickness of the carbon layer is measured at 15 arbitrary points. In such a case, it is preferable to select the measurement positions as widely and randomly as possible, without concentrating on a specific area. Finally, the average value of the thickness of the carbon layer at those 15 points is calculated.

[0119] Stoma The silicon-carbon composite may contain pores on its surface, in its interior, or both.

[0120] When the silicon-carbon composite contains pores, the pores can absorb the volumetric expansion of the silicon particles that may occur during charging and discharging of a lithium secondary battery, thereby effectively mitigating and suppressing problems caused by the volumetric expansion.

[0121] As used herein, porosity may be used interchangeably with voids, and porosity may include intrinsic porosity (also called closed porosity) and / or internal porosity.

[0122] The term "intrinsic pores" refers to pores that are independent and not connected to other pores, since the entire walls of the pores are closed to form a closed structure.

[0123] The internal porosity includes intrinsic porosity and open porosity. At least a portion of the walls of the pores may or may not be open to be connected to other pores to form an open structure. Internal porosity can also refer to pores that are exposed to the outside because they are located on the surface of the silicon-carbon composite.

[0124] On the other hand, silicon-carbon composites contain pores therein, and the porosity of the silicon-carbon composite may be 10% or less. In such cases, the porosity may refer to the internal porosity. Specifically, the porosity may be 10% or less, specifically, 0.01% to 10%, preferably 0.01% to 8%, more preferably 0.1% to 8%, and most preferably 0.5% to 5%.

[0125] If the porosity of the silicon-carbon composite exceeds the above range, the mechanical strength is reduced due to the large number of pores present in the negative electrode active material, and the negative electrode active material may collapse during the manufacturing process of the lithium secondary battery, for example, during mixing of the negative electrode active material slurry and during the roll rolling process after coating. On the other hand, if the porosity of the silicon-carbon composite is smaller than the above range, it may be difficult to manufacture the silicon-carbon composite.

[0126] When the porosity of the silicon-carbon composite satisfies the above range, it is possible to obtain a buffer effect against volume expansion while maintaining sufficient mechanical strength, and therefore it is possible to minimize the problem of volume expansion caused by the use of silicon particles, and to improve the capacity and life characteristics of lithium secondary batteries.

[0127] In addition, the volume expansion that occurs during charging and discharging of the lithium secondary battery is concentrated in the pores rather than in the outer part of the negative electrode active material, thereby effectively controlling the volume expansion and improving the life characteristics of the lithium secondary battery.In addition, the electrolyte can easily penetrate into the silicon-carbon composite, improving the charge and discharge characteristics, thereby further improving the performance of the lithium secondary battery.

[0128] The internal porosity includes the open pores on the surface of the silicon-carbon composite and the intrinsic pores.

[0129] The porosity of a silicon-carbon composite can be defined as the following Relationship 1: Porosity can refer to internal porosity.

[0130] [Equation 1] Porosity (%) = Pore volume per unit mass / (Specific volume + Pore volume per unit mass)

[0131] The measurement of the porosity is not particularly limited. According to an embodiment, the porosity may be measured by using an adsorbed gas such as nitrogen with a BELSORP (BET device) manufactured by BEL Japan Co., Ltd., or may be measured by a mercury permeation method (Hg porosimeter).

[0132] However, in the present invention, it may be difficult to measure accurate values ​​using the nitrogen adsorption method or the mercury permeation method. This may be the case when the surface of the composite is closed by a carbon coating, so that the nitrogen gas does not reach the intrinsic pores. In such a case, the porosity, i.e., the internal porosity, can be obtained by adding the value obtained by the adsorption gas (BET) such as nitrogen or the mercury permeation method and the intrinsic porosity of the following relation 2.

[0133] [Equation 2] Intrinsic porosity (%) = {1-(measured density / calculated density)} x 100

[0134] In relation 2, the density measurements may be made using helium.

[0135] In silicon-carbon composites, if the intrinsic pores are closed and nitrogen gas or mercury cannot reach the intrinsic pores, the porosity measured by nitrogen adsorption method can be considered close to the open porosity.

[0136] According to an embodiment, most of the pores formed after etching will be present in small quantities or almost non-existent after the formation of the carbon layer (post-carbon coating).

[0137] Specifically, in the method for preparing a silicon-carbon composite described below, when the carbon layer is formed, the pores present inside the composite or inside and on the surface thereof may be largely filled with carbon, so that the silicon-carbon composite may contain only a small amount of pores.

[0138] The amount of pores in the silicon-carbon composite, e.g., porosity, can be controlled in the method for preparing a silicon-carbon composite described below by adjusting the etching conditions, such as the etching solution, its concentration, and etching time, and by controlling the amount of carbon coating by changing the type of gas and coating temperature during carbon coating. The silicon-carbon composite can contain only a small number of pores or almost no pores therein through the above adjustments.

[0139] On the other hand, the silicon-carbon composite may have an intrinsic porosity of 0.01% to 8%, preferably 0.1% to 6%, and more preferably 0.5% to 5%. The intrinsic porosity may be calculated by the above-mentioned Relational Formula 2.

[0140] When the internal porosity and inherent porosity of the silicon-carbon composite satisfy the above ranges, it is possible to obtain a buffer effect against volume expansion while maintaining sufficient mechanical strength when it is applied to the negative electrode active material of a lithium secondary battery. Therefore, it is possible to minimize the problem of volume expansion caused by the use of silicon particles and to optimally improve the capacity and life characteristics.

[0141] Silicon-carbon composites can have a variety of structures.

[0142] Specifically, the silicon-carbon composites have a core-shell structure, including a silicon-carbon composite (1) having a single-layer structure in which the shell is composed of a first carbon layer, a silicon-carbon composite (2) having a multi-layer structure in which the shell includes at least two carbon layers, including a first carbon layer and a second carbon layer, and combinations thereof.

[0143] The characteristics of the silicon-carbon composite (1) and the silicon-carbon composite (2) will be specifically described below.

[0144] Silicon-carbon composite (1) The silicon-carbon composite (1) according to an embodiment may be a silicon-carbon composite having a core-shell structure with a single-layer structure in which the shell is composed of a first carbon layer.

[0145] The core structure, components and properties of the silicon-carbon composite (1) are as described above.

[0146] The first carbon layer can include at least one selected from the group consisting of amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor deposited graphene, reduced graphene oxide, and carbon nanotubes.

[0147] Specifically, the first carbon layer may use the same components as those of the first carbon layer of the silicon-carbon composite (2) described below in terms of type and properties.

[0148] The first carbon layer may be present on a surface of the core, and the first carbon layer may be present on a surface of the silicon particles and / or silicon agglomerates.

[0149] In addition, the shell is a structure that surrounds the core, and the first carbon layer contained therein suppresses the expansion of the core and the growth of silicon particles (silicon crystals) within the core, thereby further improving electrical conductivity.

[0150] The content of carbon (C) in the silicon-carbon composite (1) may be 18% by weight to 60% by weight, 20% by weight to 55% by weight, 20% by weight to 50% by weight, or 25% by weight to 45% by weight based on the total weight of the silicon-carbon composite (1). If the content of carbon (C) is less than the above range, sufficient effect of improving the conductivity cannot be expected, and the electrode life of the lithium secondary battery may be deteriorated. In addition, if the content of carbon (C) exceeds the above range, the discharge capacity of the lithium secondary battery may decrease, the bulk density may decrease, and the charge / discharge capacity per unit volume may decrease.

[0151] The amount of carbon (C) in the first carbon layer in the shell can be 2% by weight to 10% by weight, preferably 2% by weight to 8% by weight, and more preferably 3% by weight to 6% by weight, based on the total weight of the silicon-carbon composite (1).

[0152] When the amount of carbon (C) in the first carbon layer satisfies the above range, the desired effects can be effectively achieved.

[0153] The thickness of the first carbon layer can be from 2 nm to 80 nm, preferably from 3 nm to 50 nm, and more preferably from 3 nm to 30 nm.

[0154] If the thickness of the first carbon layer is smaller than the above range, the conductivity of the first carbon layer is too low, so that when applied to the negative electrode active material, the reactivity with the electrolyte increases, and the initial efficiency of the secondary battery decreases, which may cause problems. In addition, the effect of suppressing the volume expansion of silicon particles and the capacity improvement may be small, and uniform coverage may not be obtained. In addition, if the thickness of the first carbon layer exceeds the above range, the movement of lithium ions may be hindered, which may increase the resistance and reduce the adhesion strength to the core.

[0155] <Silicon-carbon composite (2)> The silicon-carbon composite (2) according to an embodiment may be a silicon-carbon composite having a core-shell structure, in which the shell has a multi-layer structure including at least two carbon layers, including a first carbon layer and a second carbon layer.

[0156] The core structure, components and properties of the silicon-carbon composite (2) are as described above.

[0157] The shell of the silicon-carbon composite (2) may include at least two carbon layers including a first carbon layer and a second carbon layer formed on the first carbon layer.

[0158] The first carbon layer may be present on a surface of the core, and the first carbon layer may be present on a surface of the silicon particles and / or silicon agglomerates.

[0159] The first carbon layer may include at least one selected from the group consisting of amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor grown graphene, reduced graphene oxide, and carbon nanotubes, where chemical vapor grown graphene refers to graphene formed by chemical pyrolysis deposition (chemical vapor deposition, CVD).

[0160] Specifically, the first carbon layer may include at least one selected from the group consisting of amorphous carbon, crystalline carbon, and chemical vapor deposition graphene. For example, when the first carbon layer is formed by disposing amorphous carbon or crystalline carbon on the core, the strength of the first carbon layer is appropriately maintained, and the expansion of the core and the growth of silicon crystals in the core can be suppressed. In addition, the conductivity of the negative electrode active material can be further improved by disposing crystalline carbon on the core to form the first carbon layer.

[0161] For example, when the carbon inside the core and the carbon of the first carbon layer on the core surface contain amorphous carbon, the thickness of the first carbon layer is preferably 2 nm or more, or 3 nm or more.

[0162] If the thickness of the first carbon layer is smaller than the above range, the effect of suppressing volume change becomes insufficient, and volume change due to charging and discharging increases, which may result in a decrease in the cycle performance of the lithium secondary battery.

[0163] In particular, according to one embodiment, when the carbon inside the core and the carbon of the first carbon layer on the core surface contain amorphous carbon, the low crystallinity further improves the buffering ability against volume expansion and further increases the electrical conductivity, thereby further improving the output characteristics and cycle characteristics of the secondary battery.

[0164] The amorphous carbon may include a material selected from the group consisting of soft carbon (low temperature calcined carbon), hard carbon, pitch carbide, mesophase pitch carbide, calcined coke, and combinations thereof.

[0165] In addition, in the Raman spectrum obtained by Raman spectroscopy of the silicon-carbon composite (1) in which the first carbon layer on the core surface contains amorphous carbon, -1 ~1,400cm -1 The intensity of the D band peak appearing in the range of 1,500 cm -1 ~1,660cm -1 If the intensity of the G-band peak appearing in the range is IG, the following relational expression 3 is satisfied.

[0166] [Equation 3] ID / IG>3 ID / IG is preferably 3-5, and more preferably 3-4.

[0167] The G-band peak, for example, is at about 1,550 cm -1 ~Approx. 1,610cm -1 (For example, 1,580 cm -1 The D band peak has a Raman shift of, for example, about 1,290 cm -1 ~Approx. 1,350cm -1 (For example, 1,320 cm -1 The peak has a Raman shift of about 100 nm (around 100 nm), which can be attributed to amorphous carbon.

[0168] That is, the value of ID / IG may represent the ratio of amorphous carbon to graphite in the carbon layer. The value of ID / IG may also indicate the crystallinity of the carbon layer. A high ID / IG value may indicate a high proportion of amorphous carbon.

[0169] If ID / IG is smaller than the above range, the cycle characteristics of the secondary battery may deteriorate.

[0170] The Raman spectrum is measured using a micro-Raman spectrometer (Nicolet Almega Ga XR manufactured by Thermo Fisher Scientific) with a laser wavelength of 780 nm.

[0171] In the Raman spectrum of the first carbon layer, the intensities of the D band peak and the G band peak can be obtained as follows.

[0172] The Raman spectrum, which is composed of the sum of the D-band peak and the G-band peak, is split into two peaks, which are fitted to a Gaussian function or a mixed Gaussian / Lorentzian function using the nonlinear least squares method. The integrated intensities of the resulting D-band and G-band are calculated, and the peak intensities of the split D-band peak and G-band peak are calculated, respectively.

[0173] Crystalline carbon, on the other hand, can include, but is not limited to, natural graphite, synthetic graphite, expanded graphite, graphene, carbon black, fullerene soot, or combinations thereof.

[0174] Natural graphite can be graphite that occurs in nature, which can include flake graphite, highly crystalline graphite, microcrystalline or cryptocrystalline (amorphous) graphite, and the like.

[0175] Artificial graphite is an artificially synthesized graphite, which is made by heating amorphous carbon at high temperatures. It can be primary graphite, electrographite, secondary graphite, graphite fiber, etc. Expandable graphite is made by intercalating chemicals such as acids or alkalis between the layers and heating them to solidify the vertical layers of its molecular structure. Graphene refers to a single layer of graphite.

[0176] A second carbon layer may be present on the first carbon layer.

[0177] The second carbon layer may comprise at least one selected from the group consisting of amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor deposited graphene, reduced graphene oxide, and carbon nanotubes, in which case the first carbon layer and the second carbon layer comprise different types.

[0178] According to an embodiment, in the silicon-carbon composite (2), the first carbon layer may comprise at least one selected from the group consisting of amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor deposition graphene, and carbon nanotubes, and the second carbon layer may comprise reduced graphene oxide (RGO).

[0179] Reduced graphene oxide can be formed by partially or substantially completely reducing graphene oxide.

[0180] When the second carbon layer comprises reduced graphene oxide, it can function as a barrier layer or buffer layer, which is effective as a mechanical buffer support surrounding the core and can improve adhesion to the binder. More specifically, the buffer layer can suppress degradation, crack formation, and volume expansion of the core caused by the mechanical expansion of silicon during charging and discharging.

[0181] When the silicon-carbon composite (2) is used as a negative electrode active material, the contact resistance between the negative electrode active material layer and the current collector and between the negative electrode active material particles themselves can be reduced, thereby improving the lithium intercalation and desorption characteristics.

[0182] Additionally, the second carbon layer may further comprise graphite.

[0183] According to an embodiment, in a silicon-carbon composite, a first carbon layer and a second carbon layer may be sequentially disposed on a core to form a shell.

[0184] The first carbon layer may be formed using a chemical pyrolytic deposition method (chemical vapor deposition, CVD). The second carbon layer may be formed using one or more methods selected from a liquid coating method and a spray drying method.

[0185] Specifically, in the silicon-carbon composite (2), a first carbon layer may be formed on a core by chemical pyrolysis deposition, and then a second carbon layer comprising reduced graphene oxide may be formed on the first carbon layer using one or more methods selected from liquid coating and spray drying.

[0186] When the first carbon layer is formed on the core by chemical pyrolysis deposition, the carbon (carbon layer) can be formed mainly in the pores in the core. When the carbon is uniformly formed in the inherent pores, it is possible to minimize the volume expansion of silicon during charging and discharging and the formation of large silicon particles caused by the sintering of nanosilicon due to the volume expansion.

[0187] On the other hand, when a second carbon layer containing reduced graphene oxide is formed on a first carbon layer by using at least one method selected from a liquid coating method and a spray drying method, the carbon content can be easily controlled according to the purpose, and a low specific surface area, high electrical conductivity, high capacity, and long life can be achieved.

[0188] In the silicon-carbon composite (2), the carbon layers forming the shell can be laminated in various ways as long as the desired effect is not impaired. This can be up to 4 layers, specifically 2 to 4 layers, preferably 2 to 3 layers, for example 2 layers.

[0189] When a silicon-carbon composite (2) in which at least two carbon layers are formed sequentially on the entire, most or part of the surface of a core is used as an anode active material, it is possible to suppress the release of lithium from the core and the volume change of silicon particles that occurs during lithium intercalation and deintercalation, thereby maintaining high conductivity and conductive paths between the particles of the anode active material. As a result, it is possible to provide an anode active material and a lithium secondary battery having high charge / discharge capacity and excellent cycle life characteristics.

[0190] The content of carbon (C) in the silicon-carbon composite (2) can be 18% by weight to 60% by weight, 20% by weight to 60% by weight, 20% by weight to 55% by weight, or 30% by weight to 55% by weight, based on the total weight of the silicon-carbon composite (2).

[0191] If the carbon (C) content in the silicon-carbon composite (2) is less than the above range, the effect of suppressing the volume expansion of the negative electrode active material and improving its electrical conductivity may be small, and if the carbon (C) content exceeds the above range, problems may occur in that the capacity of the secondary battery may decrease and lithium ions may hardly be released.

[0192] The carbon (C) content contained in the core of the silicon-carbon composite (2) may be the carbon (C) content contained in the core of a silicon-carbon composite.

[0193] In the shell of the silicon-carbon composite (2), the amount of carbon (C) in the first carbon layer can be 2 wt % to 10 wt %, preferably 2 wt % to 8 wt %, and more preferably 3 wt % to 6 wt %, based on the total weight of the silicon-carbon composite (2).

[0194] Furthermore, in the shell of the silicon-carbon composite (2), the amount of carbon (C) in the second carbon layer can be 2 wt % to 10 wt %, preferably 2 wt % to 8 wt %, more preferably 2 wt % to 6 wt %, and even more preferably 2 wt % to 5 wt %, based on the total weight of the silicon-carbon composite (2).

[0195] If the content of carbon (C) in the second carbon layer is less than the above range, problems may occur in that the effect of suppressing the volume expansion of the negative electrode active material and improving its conductivity may be small. If the content of carbon (C) in the second carbon layer is more than the above range, problems may occur in that the capacity of the secondary battery may decrease and lithium ions may hardly be released.

[0196] Specifically, the shell allows lithium to pass through but prevents oxygen from passing through. This prevents oxygen from reacting with the silicon and / or silicon oxide compounds in the core. In addition, when the shell is uniformly coated and formed on the core, it has the effect of suppressing the generation of cracks caused by stress due to the sudden volume expansion of silicon. Since the cracks are formed irregularly and discontinuously, the electrolyte does not contact the inside of the negative electrode active material, or there are parts that are electrically cut off, which may cause secondary battery failure. In this regard, the role of the reduced graphene oxide of the second carbon layer is important. Since the reduced graphene oxide has high electrical conductivity, the carbon layer can maintain an electrically connected state.

[0197] On the other hand, the total thickness of the first carbon layer and the second carbon layer can be 5 nm to 100 nm, preferably 5 nm to 80 nm, more preferably 5 nm to 50 nm. When the total thickness of the first carbon layer and the second carbon layer satisfies the above range, even if the volume of the core changes due to the intercalation and desorption of lithium, it is possible to effectively prevent or mitigate the crushing of the core, and to effectively prevent or mitigate the side reaction between silicon and the electrolyte, thereby improving the performance of the secondary battery.

[0198] Specifically, the thickness of the first carbon layer may be 2 nm to 50 nm, preferably 2 nm to 40 nm, more preferably 3 nm to 30 nm. If the thickness of the first carbon layer is smaller than the above range, the conductivity of the first carbon layer is too low, so that when applied to a negative electrode active material, the reactivity with the electrolyte increases, and the initial efficiency of the secondary battery decreases, which may cause problems. Furthermore, the effect of suppressing the volume expansion of silicon particles and the capacity improvement may be slight, and uniform coverage may not be obtained. In addition, if the thickness of the first carbon layer exceeds the above range, the movement of lithium ions may be hindered, which may increase the resistance, and the adhesive strength to the core may decrease.

[0199] The thickness of the second carbon layer may be 3 nm to 50 nm, preferably 3 nm to 30 nm, more preferably 5 nm to 20 nm. If the thickness of the second carbon layer is smaller than the above range, the conductivity of the second carbon layer is too low, so that when applied to a negative electrode active material, the reactivity with the electrolyte increases, and the initial efficiency decreases. In addition, the effect of suppressing the volume expansion of silicon particles and the capacity improvement become small, and uniform coating may not be obtained. If the thickness of the second carbon layer exceeds the above range, the thickness of the second carbon layer becomes too large, which may hinder the movement of lithium ions, which may increase the resistance and may decrease the adhesion strength to the core.

[0200] In the silicon-carbon composite (2), the carbon layer including at least two carbon layers is preferably formed so that each carbon layer is formed thinly and uniformly along the entire outer shape of the shell while maintaining the outer shape of the shell. However, a part or most of the carbon layer may be formed to cover the entire surface of the core. When the first carbon layer and the second carbon layer are each formed thinly and uniformly on the surface of the core, the electrical contact between the particles contained in the negative electrode active material can be improved.

[0201] Silicon-carbon composite (2) is 2m 2 / g~30m 2 / g, 2m 2 / g~20m 2 / g, or 2m 2 / g~10m 2 / g specific surface area (Brunauer-Emmett-Teller; BET).

[0202] In addition, in the Raman spectrum obtained by Raman spectroscopy of the silicon-carbon composite (2), -1 ~2,760cm -1 The intensity of the 2D band peak appearing in the range of 1,500 cm is defined as I2D. -1 ~1,660cm -1 The intensity of the G-band peak appearing in the range of 1,280 cm -1 ~1,400cm -1If the D band peak appearing in the range is ID, the following relation 4 is satisfied.

[0203] [Equation 4] 0.5<(I2D+IG) / ID≦2.0

[0204] The content of oxygen (O) in the reduced graphene oxide in the second carbon layer may be 0.5 wt% to 10 wt%, preferably 1 wt% to 10 wt%, more preferably 3 wt% to 10 wt%, based on the total weight of the reduced graphene oxide. When the content of oxygen (O) in the reduced graphene oxide in the second carbon layer satisfies the above range, the degree of reduction of the graphene oxide increases, and thus reduced graphene oxide with high electrical conductivity can be obtained, thereby further improving the effect of the lithium secondary battery.

[0205] The reduced graphene oxide in the second carbon layer may contain at least one selected from the group consisting of lithium (Li), sodium (Na) and potassium (K) in an amount of 0.1 wt% to 5 wt%, preferably 0.1 wt% to 4 wt%, more preferably 0.1 wt% to 3 wt%, based on the total weight of carbon (C) in the second carbon layer. When the reduced graphene oxide of the second carbon layer contains at least one selected from the group consisting of lithium (Li), sodium (Na) and potassium (K) in the above content, it may be even more advantageous to obtain the desired effect.

[0206] The silicon-carbon composite (2) may have an electrode expansion rate of 50% to 150%, preferably 50% to 100%, and more preferably 55% to 80% by weight based on the thickness of the electrode after one charge / discharge cycle.

[0207] The silicon-carbon composite (2) includes at least two carbon layers including a first carbon layer and a second carbon layer, thereby further increasing the strength of the shell layer, increasing the bond (adhesion) between the silicon-carbon composite (2) and the binder, resulting in a reduction in the electrode expansion rate, and improving the capacity retention rate after cycling (e.g., after 100 cycles) of the lithium secondary battery.

[0208] [Method for preparing silicon-carbon composites] A method for preparing a silicon-carbon composite according to one embodiment includes a first step of etching a silicon-based raw material powder with an etching solution containing a fluorine (F) atom-containing compound, a second step of filtering and drying a product obtained by the etching to prepare a silicon composite, and a third step of coating the inside of the silicon composite with carbon, or coating the inside of the silicon composite with carbon and forming a carbon layer on its surface, to obtain a silicon-carbon composite.

[0209] Specifically, in a method for preparing a silicon-carbon composite, the first step may involve etching a silicon-based raw material powder with an etching solution containing a fluorine (F) atom-containing compound.

[0210] The silicon-based raw material powder may include a powder containing silicon capable of reacting with lithium, such as a powder containing two or more of silicon, silicon oxide, and silicon dioxide.

[0211] The etching process may include dry etching and wet etching.

[0212] When dry etching is used, selective etching may be possible.

[0213] The silicon dioxide of the silicon-based raw material powder is dissolved and eluted by the etching process, thereby forming pores.

[0214] The pores can also be considered to be formed by the following reaction schemes 2 and 3.

[0215] [Reaction Scheme 2] SiO2+4HF(gas) →SiF4+2H2O

[0216] [Reaction Scheme 3] SiO2+6HF(aqueous solution) →H2SiF6+2H2O

[0217] Silicon dioxide can be dissolved and removed in the form of SiF4 and H2SiF6 through a reaction mechanism such as the reaction scheme above, forming pores (voids).

[0218] Furthermore, silicon dioxide contained in the silicon composite may be removed depending on the degree of etching, and pores may be formed therein.

[0219] Here, etching refers to a process of treating a silicon-based raw material powder with an etching solution containing a fluorine (F) atom-containing compound.

[0220] The etching solution containing a fluorine (F) atom-containing compound is not limited as long as the effect is not impaired, and any commonly used fluorine atom-containing etching solution can be used.

[0221] Specifically, the fluorine (F) atom-containing compound may include at least one selected from the group consisting of HF, NH4F, and HF2. The use of the fluorine (F) atom-containing compound may allow the etching process to be carried out more quickly.

[0222] The etching solution may further comprise one or more acids selected from the group consisting of organic acids, sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, and chromic acid.

[0223] As etching conditions, the stirring temperature (treatment temperature) can be, for example, 10°C to 90°C, preferably 10°C to 80°C, and more preferably 20°C to 70°C.

[0224] The silicon composite may have some residual silicon oxide and some residual silicon dioxide.

[0225] Specifically, the content of silicon dioxide in the silicon composite may be 0.1 to 5% by weight, preferably 0.2 to 5% by weight, and more preferably 0.5 to 4% by weight. A negative electrode active material containing a composite containing silicon dioxide in the above range is preferable because it has good charge / discharge cycle characteristics and can provide a lithium secondary battery having a high battery capacity.

[0226] In addition, the number of oxygen atoms present on the surface of the silicon composite can be reduced by etching. That is, the oxygen fraction on the surface of the silicon composite can be significantly reduced by etching, and the surface resistance can be reduced. As a result, when the silicon-carbon composite is applied to the negative electrode active material, the electrochemical properties of the lithium secondary battery, particularly the life characteristics, can be significantly improved.

[0227] According to one embodiment, the etching removes silicon dioxide, thereby significantly reducing the oxygen concentration, and therefore the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) in silicon composites and silicon-carbon composites.

[0228] On the other hand, pores may be formed in the areas where the silicon dioxide has been removed by etching. Specifically, the silicon composite may be porous after etching and before carbon coating.

[0229] Another feature is that the average grain size of the silicon composite is hardly changed by etching.

[0230] Also, selective etching may be performed according to the desired purpose. Since the selective etching removes a large amount of silicon dioxide, silicon (Si) may be contained at a very high fraction compared to oxygen (O). In particular, the surface of the etched silicon particles may contain oxygen (O) at a very low fraction compared to silicon (Si). In such a case, it is possible to obtain a lithium secondary battery having an excellent capacity retention rate and improved discharge capacity and initial efficiency.

[0231] In the method for preparing the silicon-carbon composite, the second step may include filtering and drying the product obtained by etching to obtain the silicon composite. The filtering and drying steps may be carried out by a commonly used method.

[0232] In the method for preparing the silicon-carbon composite, the third step may include forming a carbon layer on the surface of the silicon composite by chemical pyrolysis deposition to obtain the silicon-carbon composite.

[0233] The electrical contact between the silicon-carbon composite particles can be improved by the carbon layer forming step in the third step, and when charging and discharging, excellent electrical conductivity can be obtained even after the electrode expands, which can further improve the performance of the lithium secondary battery.

[0234] Specifically, the carbon layer can increase the electrical conductivity of the negative electrode active material to improve the output characteristics and cycle characteristics of the battery, and can promote stress relaxation when the volume of the active material changes.

[0235] The carbon layer may comprise at least one selected from the group consisting of graphene, reduced graphene oxide, carbon nanotubes, carbon nanofibers, and graphite.

[0236] The carbon layer in the third step can be formed by injecting at least one compound selected from the compounds represented by the following formulas 1 to 3, and carrying out the reaction at 400° C. to 1,200° C. in a gaseous state.

[0237] [Formula 1] C N H (2N+2-A) [OH] A In formula 1, N is an integer of 1 to 20, and A is 0 or 1.

[0238] [Formula 2] C N H (2N-B) In formula 2, N is an integer from 2 to 6, and B is an integer from 0 to 2.

[0239] [Formula 3] C x H y O z In formula 3, x is an integer from 1 to 20, y is an integer from 0 to 25, and z is an integer from 0 to 5.

[0240] For example, the third step may include injecting at least one compound selected from the compounds represented by the following formulas 1 to 3, and carrying out the reaction in a gaseous state at 400° C. to 1,200° C. to form carbon in the core and a first carbon layer in the shell.

[0241] That is, by carrying out the third step, it is possible to obtain a silicon-carbon composite (1) having a core-shell structure in which the core contains silicon particles and carbon, and the shell contains a carbon layer (first carbon layer).

[0242] The compound represented by formula 1 may be at least one selected from the group consisting of methane, ethane, propane, butane, methanol, ethanol, propanol, propanediol, and butanediol. The compound represented by formula 2 may be at least one selected from the group consisting of ethylene, acetylene, propylene, butylene, butadiene, and cyclopentene. The compound represented by formula 3 may be at least one selected from the group consisting of benzene, toluene, xylene, ethylbenzene, naphthalene, anthracene, and dibutylhydroxytoluene (BHT).

[0243] A carbon coating may also be formed uniformly on the surfaces of the pores inside the silicon-carbon composite, which is preferred as it further improves the cycle life.

[0244] The carbon source gas may further contain at least one inert gas selected from hydrogen, nitrogen, helium, and argon. The reaction may be carried out at, for example, 400°C to 1,200°C, specifically 500°C to 1,100°C, more specifically 600°C to 1,000°C.

[0245] The reaction time (or heat treatment time) can be appropriately adjusted depending on the heat treatment temperature, the pressure during the heat treatment, the composition of the gas mixture, and the amount of carbon coating desired. For example, the reaction time can be, but is not limited to, 10 minutes to 100 hours, specifically 30 minutes to 90 hours, and more specifically 50 minutes to 40 hours.

[0246] In a method for preparing a silicon-carbon composite according to an embodiment, a thin and uniform carbon layer containing amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor grown graphene, reduced graphene oxide or carbon nanotubes as a main component can be formed on the surface of a silicon composite by a gas phase reaction of a carbon source gas even at a relatively low temperature. Furthermore, desorption reaction does not substantially occur in the carbon layer thus formed.

[0247] Furthermore, the gas phase reaction allows carbon to be formed uniformly throughout the interior and surface of the silicon composite, resulting in the formation of a carbon film (carbon layer) with high crystallinity.

[0248] Therefore, when the silicon-carbon composite is used as a negative electrode active material, the electrical conductivity of the negative electrode active material can be improved without changing the structure.

[0249] Also, according to an embodiment, when a reactive gas containing a carbon source gas and an inert gas is supplied to the silicon composite, the reactive gas penetrates into the open pores of the silicon composite, and conductive carbon materials, such as one or more graphene-containing materials selected from graphene, reduced graphene oxide, and graphene oxide, carbon nanotubes, and carbon nanofibers, grow on the surface of the silicon composite.

[0250] For example, as the reaction time passes, the conductive carbon material deposited on the silicon surface in the silicon composite gradually grows to obtain a silicon-carbon composite.

[0251] On the other hand, according to certain embodiments, the specific surface area of ​​the silicon-carbon composite may be decreased depending on the amount of carbon coating.

[0252] The structure of the graphene-containing material can be of layer, nanosheet type, or a mixture of several flakes.

[0253] When a carbon layer containing a graphene-containing material is uniformly formed over the entire surface of a silicon composite, the graphene-containing material, which has improved electrical conductivity and is flexible against volume expansion, grows directly on the surface of the silicon particles, thereby suppressing volume expansion. The carbon layer coating can also reduce the possibility of silicon coming into direct contact with the electrolyte, thereby reducing the formation of a solid electrolyte interface (SEI) layer. The carbon present in the silicon-carbon composite can also be uniformly present inside and / or on the surface of the composite.

[0254] According to an embodiment, the process of forming the carbon coating layer allows most of the open and closed pores present in the interior and surface of the silicon composite to be filled with carbon. As a result, the porosity of the silicon-carbon composite can be significantly reduced. That is, the silicon-carbon composite may have no pores or may have a small number of pores. For example, since the silicon-carbon composite has almost no pores, the strength and density of the silicon-carbon composite are increased, which can increase the discharge capacity per volume of a lithium secondary battery.

[0255] If pores are present in the silicon-carbon composite after carbon coating, the porosity is as described above.

[0256] Additionally, according to some embodiments, the silicon-carbon composite may have a three-dimensional (3D) structure in which the silicon-carbon composite particles are coalesced together.

[0257] Meanwhile, the method for preparing a silicon-carbon composite according to an embodiment may further include a fourth step of forming a second carbon layer on the first carbon layer by using a liquid coating method after forming the first carbon layer.

[0258] In the method for preparing a silicon-carbon composite, when it includes the first to third steps, a silicon-carbon composite (1) including a first carbon layer can be obtained, and when it includes the first to fourth steps, a silicon-carbon composite (2) including a first carbon layer and a second carbon layer can be obtained.

[0259] Specifically, referring back to FIG. 1, the silicon composite of FIG. 1(B) can be obtained by a first etching step and a second step of filtering and drying the product obtained by etching.

[0260] For example, as shown in FIG. 1(B), the silicon composite may include silicon particles (20) and a plurality of pores (10).

[0261] Silicon dioxide contained in the silicon composite may be removed depending on the degree of etching, and pores may be formed therein.

[0262] In addition, the number of oxygen atoms present on the surface of the silicon composite can be reduced by etching. That is, the oxygen fraction on the surface of the silicon composite can be significantly reduced by etching, and the surface resistance can be reduced. As a result, when the silicon-carbon composite is applied to the negative electrode active material, the electrochemical properties of the lithium secondary battery, particularly the life characteristics, can be significantly improved.

[0263] On the other hand, the silicon-carbon composite (1) in Fig. 1(C) can be obtained by the third step ((1) in Fig. 1) using a chemical pyrolysis deposition method. In such a case, in the silicon-carbon composite (1), carbon may be coated inside the silicon composite, or carbon may be coated inside the silicon composite and a carbon layer (first carbon layer) may be formed on the surface thereof.

[0264] Specifically, the silicon-carbon composite (1) formed by the third step may include silicon particles (20), specifically silicon agglomerates in which the silicon particles (20) are coalesced (or interconnected) with one another, and the carbon layer (first carbon layer) (40) may be formed on the surface of the silicon particles, and the carbon (45) may be formed such that it is uniformly dispersed and / or distributed among the silicon particles (20). Also, the silicon-carbon composite (1) may include pores (10) therein.

[0265] In the third step, when the carbon layer (first carbon layer) is formed using a chemical pyrolysis deposition method, most of the pores inside the silicon composite are filled with carbon or are uniformly coated with, for example, an amorphous carbon layer, which has the advantage that the volume expansion of silicon and / or sintering of silicon during discharge is suppressed.

[0266] The electrical contact between the particles of the silicon-carbon composite (1) can be improved by the carbon layer (first carbon layer) formation step in the third step. Furthermore, when charging and discharging are performed, excellent electrical conductivity can be imparted even after the electrode expands, which can further improve the performance of the lithium secondary battery.

[0267] Furthermore, a fourth step ((2) in FIG. 1) using a liquid coating method can be used to obtain a silicon-carbon composite (2) in FIG. 1(D) in which a second carbon layer is formed on the first carbon layer.

[0268] Specifically, the silicon-carbon composite (2) prepared by the fourth step may have a core-shell structure, where the core may include silicon particles (20) and carbon (45), and the shell may include a first carbon layer (40) and a second carbon layer (50) on the first carbon layer (40). Also, the silicon-carbon composite (2) may include pores (10) therein.

[0269] The second carbon layer can be formed using reduced graphene oxide. The reduced graphene oxide can be formed by partially or substantially completely reducing graphene oxide. Specifically, the second carbon layer can be formed on the surface of the first carbon layer from reduced graphene oxide via partial π-π bonds or physical bonds between the carbon-carbon layers while drying in a spray dryer.

[0270] The second carbon layer may be formed using one or more methods selected from a dry coating method and a liquid coating method.

[0271] Specifically, the second carbon layer can be formed by using the spray drying method of the liquid coating method.When the second carbon layer is formed by using the spray drying method, unlike the chemical pyrolysis deposition method, it is possible to control the carbon content by adjusting the concentration of reduced graphene oxide and to perform coating at low temperature, and the increase in the crystal size of silicon caused by carbon coating at high temperature will not occur.

[0272] In forming the second carbon layer, graphene oxide or reduced graphene oxide is dispersed in a solvent to prepare a dispersion, and the concentration of the dispersion may be 0.01 to 50 mg / ml.

[0273] The temperature in the spray drying may be 100° C. to 500° C., specifically 150° C. to 350° C. When the spray drying is performed at the above temperature using graphene oxide, the graphene oxide can be reduced to form reduced graphene oxide.

[0274] That is, in preparing the silicon-carbon composite (2), the first carbon layer can be formed using a chemical pyrolysis deposition method, and the second carbon layer can be formed using a spray drying method.

[0275] The oxygen content of the second carbon layer can be adjusted by subjecting the second carbon layer formed by the spray drying method to a heat treatment at 500° C. to 800° C. in an inert gas.

[0276] On the other hand, according to some embodiments, once the first carbon layer or the second carbon layer is formed in any one or more of the third and fourth steps, a further step of at least one of grinding and classifying the silicon-carbon composite to a desired average particle size may be performed.

[0277] For example, after forming the first carbon layer in the third step, one or more of the silicon composite powders may be combined with one another to form aggregates, and the method may further include grinding and classifying the silicon-carbon composite so that the average particle size of the silicon-carbon composite is 2 μm to 15 μm. Classification may be performed to adjust the particle size distribution of the silicon-carbon composite, and may involve dry classification, wet classification, or sieving.

[0278] In dry classification, the processes of dispersion, separation, collection (separation of solids and gas), and discharge are carried out sequentially or simultaneously using an air flow, and the moisture or oxygen concentration in the air flow used may be adjusted by performing pretreatment (adjusting moisture, dispersibility, humidity, etc.) before classification to prevent a decrease in classification efficiency due to interference between particles, particle shape, airflow turbulence, velocity distribution, static electricity, and the like.

[0279] Alternatively, the desired particle size distribution can be obtained by performing pulverization and classification at the same time. After pulverization, it is effective to separate the coarse powder from the granular part using a classifier or a sieve.

[0280] Specifically, once the first carbon layer and / or the second carbon layer are formed, a milling process may be performed.

[0281] Alternatively, at least one step of pulverizing and classifying the silicon-carbon composite having a core-shell structure obtained in the fourth step may be further carried out (fifth step).

[0282] According to an embodiment, the silicon-carbon composite having a core-shell structure is subjected to crushing and / or classification, so that a silicon-carbon composite having a desired average particle size can be obtained.

[0283] Specifically, in the fifth step, the silicon-carbon composite (2) obtained in the fourth step may be classified. Alternatively, the silicon-carbon composite (2) may be pulverized. Alternatively, the silicon-carbon composite (2) may be pulverized and classified. Specifically, the silicon-carbon composite (2) obtained in the fourth step may be classified and, if necessary, pulverized. Alternatively, the silicon-carbon composite (2) obtained in the fourth step may be pulverized.

[0284] According to the above-mentioned preparation method, it is possible to provide a silicon-carbon composite containing silicon particles and carbon, and having a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms within a specific range. When this silicon-carbon composite is used as the negative electrode active material to manufacture a lithium secondary battery, it is possible to significantly improve the discharge capacity and initial efficiency as well as the excellent capacity retention rate.

[0285] In addition, when the silicon-carbon composite contains at least one carbon layer, it is possible to ensure sufficient electrical conductivity and to appropriately adjust the specific surface area. This can improve the performance of lithium secondary batteries. Furthermore, by changing the shell structure of the silicon-carbon composite, the characteristics of the secondary battery can be controlled.

[0286] In particular, the silicon-carbon composite includes at least two carbon layers including a first carbon layer and a second carbon layer, which further increases the strength, increases the bond (adhesion) between the silicon-carbon composite (2) and the binder, leads to a reduction in the electrode expansion rate, and further improves the capacity retention rate after cycling of the lithium secondary battery.

[0287] Additionally, the preparation method according to an embodiment has the advantage that it allows for mass production by a continuous process with minimal steps.

[0288] The silicon-carbon composite prepared by the above preparation method can be advantageously used in negative electrode active materials and lithium secondary batteries, and can efficiently achieve the desired effects.

[0289] [Negative electrode active material] A negative electrode active material according to some embodiments can include a silicon-carbon composite.

[0290] The negative electrode active material may further include a carbon-based negative electrode material, specifically a graphite-based negative electrode material.

[0291] The negative electrode active material may be a mixture of the silicon-carbon composite and a carbon-based negative electrode material, such as a graphite-based negative electrode material, which can reduce the electrical resistance of the negative electrode active material and at the same time, can alleviate the expansion stress caused by charging.

[0292] The carbon-based negative electrode material may include, for example, at least one selected from the group consisting of natural graphite, synthetic graphite, soft carbon, hard carbon, mesocarbon, carbon fiber, carbon nanotubes, pyrolytic carbon, coke, glass carbon fiber, sintered organic polymer compounds, and carbon black.

[0293] The content of the carbon-based negative electrode material can be 10% by weight to 95% by weight, preferably 30% by weight to 90% by weight, and more preferably 30% by weight to 80% by weight, based on the total weight of the negative electrode active material.

[0294] Furthermore, when a silicon-carbon composite containing silicon particles with a crystallite size of 2 nm to 10 nm is mixed with a graphite-based material, which generally has a small volume expansion, a lithium secondary battery with excellent cycling characteristics can be obtained because the silicon particles alone do not cause a large volume expansion.

[0295] The negative electrode active material may further include silicon powder having a surface coated with carbon, and a composite composed of silicon powder and graphite.

[0296] According to one embodiment, there is provided a negative electrode including the negative electrode active material, and a lithium secondary battery including the same.

[0297] A lithium secondary battery can include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and a non-aqueous liquid electrolyte having a lithium salt dissolved therein, where the negative electrode can include a negative electrode active material including a silicon-carbon composite.

[0298] The negative electrode may be composed of only the negative electrode mixture, or may be composed of a negative electrode current collector and a negative electrode mixture layer (negative electrode active material layer) supported thereon. Similarly, the positive electrode may be composed of only the positive electrode mixture, or may be composed of a positive electrode current collector and a positive electrode mixture layer (positive electrode active material layer) supported thereon. In addition, the negative electrode mixture and the positive electrode mixture may each further contain a conductive agent and a binder.

[0299] The materials constituting the negative electrode current collector and the positive electrode current collector may be materials known in the art. The binder and conductive material added to the negative electrode and the positive electrode may be materials known in the art.

[0300] When the negative electrode is composed of a current collector and an active material layer supported thereon, the negative electrode can be prepared by coating the surface of the current collector with a negative electrode active material composition containing a silicon-carbon composite and drying it.

[0301] Lithium secondary batteries also include a non-aqueous liquid electrolyte, where the non-aqueous liquid electrolyte may include a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.

[0302] Solvents commonly used in the art may be used as the non-aqueous solvent. Specifically, aprotic organic solvents may be used.

[0303] Examples of aprotic organic solvents include cyclic carbonates such as ethylene carbonate, propylene carbonate, and butylene carbonate, cyclic carboxylic acid esters such as furanone, chain carbonates such as diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate, chain ethers such as 1,2-methoxyethane, 1,2-ethoxyethane, and ethoxymethoxyethane, and cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran. These may be used alone or in combination of two or more.

[0304] The lithium secondary battery may include a non-aqueous lithium secondary battery.

[0305] A negative electrode active material and a lithium secondary battery using the silicon-carbon composite according to an embodiment can improve charge / discharge capacity, initial charge / discharge efficiency, and capacity retention rate.

[0306] The present invention will be described in detail below with reference to examples. The following examples are merely illustrative of the present invention, and the scope of the present invention is not limited thereto. EXAMPLES

[0307] <Example 1> Preparation of silicon-carbon composites (1) Step 1: Silicon oxide (SiO ) having the physical properties shown in Table 1 below, prepared by vapor phase growth method using silicon powder and silicon dioxide powder. x , x=1.01) powder (50 g) was dispersed in 50 g of water, stirred at 300 rpm, and 110 ml of a 40 wt % HF aqueous solution was added as an etching solution, thereby etching the silicon-based raw material powder for 1 hour.

[0308] (2) Step 2: The product obtained by the above etching was filtered and dried at 100° C. for 2 hours.

[0309] Next, in order to control the particle size of the complex, the complex was pulverized using a mortar so that the average particle size was about 5 μm, thereby preparing a silicon complex (B1).

[0310] (4) Step 3: 10 g of the silicon composite was placed in a tubular electric furnace, and argon (Ar) and methane gas were flowed at a rate of 1 L / min each. It was maintained at 900°C for 1 hour, and then cooled to room temperature. As a result, the surface of the silicon composite was coated with carbon, and a silicon-carbon composite having the contents and physical properties of each component shown in Table 3 below was prepared.

[0311] In order to control the particle size of the silicon-carbon composite, the silicon-carbon composite was mechanically crushed and classified to have an average particle size of about 5 μm, thereby preparing silicon-carbon composite (1).

[0312] Fabrication of lithium secondary batteries A negative electrode and a battery (coin cell) containing the silicon-carbon composite (1) as the negative electrode active material were prepared.

[0313] The negative electrode active material, Super-P as a conductive material, and polyacrylic acid were mixed with water in a weight ratio of 80:10:10 to prepare a negative electrode active material composition with a solid content of 45%.

[0314] The negative electrode active material composition was applied to a copper foil having a thickness of 18 μm and dried to prepare an electrode having a thickness of 70 μm. The copper foil covered with the electrode was punched out into a circle having a diameter of 14 mm to prepare a negative electrode for a coin cell.

[0315] On the other hand, a metallic lithium foil having a thickness of 0.3 mm was used as the positive electrode.

[0316] A porous polyethylene sheet with a thickness of 25 μm was used as the separator. A liquid electrolyte in which LiPF6 was dissolved at a concentration of 1 M in a mixed solvent of ethylene carbonate (EC) and diethylene carbonate (DEC) in a volume ratio of 1:1 was used as the electrolyte. A coin cell (battery, CR2032) was fabricated using the above components.

[0317] <Examples 2 to 7> Silicon-carbon composites (1) were prepared by carrying out the same method as in Example 1, except that the silicon-based raw material powders (A) and silicon composites (B) shown in Tables 1 and 2 below were used, the type and amount of carbon source gas were changed as shown in Table 3, and the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite was changed. A negative electrode active material and a lithium secondary battery were produced using the silicon-carbon composites (1).

[0318] <Example 8> A silicon-carbon composite (2) having a second carbon layer formed on the surface of the first carbon layer of the silicon-carbon composite (1) prepared in Example 2 using a spray dryer was obtained.

[0319] The formation of the second carbon layer by the spray dryer is as follows.

[0320] (1) to (3) Steps 1 to 3: The same procedures as in Example 2 were carried out.

[0321] (4) Step 4: A graphene oxide dispersion was prepared by adding the silicon-carbon composite having the first carbon layer obtained in Example 2 to 0.5 wt % graphene oxide in the same weight ratio. The dispersion was injected at 100 ml / min using a metering pump, and spray-dried at a dispersion concentration of 1.0 mg / ml and a spray temperature of 250° C., thereby obtaining a silicon-carbon composite having two layers including a first carbon layer and a second carbon layer.

[0322] (5) Step 5: In order to control the particle size of the silicon-carbon composite, the average particle size (D 50The final silicon-carbon composite (2) was prepared by mechanically crushing and classifying the resulting silicon-carbon composite (2).

[0323] A negative electrode active material and a lithium secondary battery were produced in the same manner as in Example 1 using the silicon-carbon composite (2).

[0324] <Example 9> A silicon-carbon composite (2) was prepared by carrying out the same method as in Example 8, except that a spray dryer was used on the first carbon layer of the silicon-carbon composite (1) prepared in Example 4, and the components and properties were adjusted to be those shown in Table 4. A negative electrode active material and a lithium secondary battery were produced using the silicon-carbon composite (2).

[0325] <Comparative Example 1> A negative electrode active material and a lithium secondary battery using the same were produced in the same manner as in Example 1, except that the etching process in step 1 using the etching solution in Example 1 was not carried out.

[0326] <Comparative Examples 2 to 4> A silicon-carbon composite was prepared by carrying out the same method as in Example 1, except that a silicon composite (B) having the atomic content and physical properties shown in Table 2 below was used, the type and amount of carbon source gas was changed as shown in Table 3, and the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) in the silicon-carbon composite was changed, and a lithium secondary battery was manufactured using the silicon-carbon composite.

[0327] Test Example <Test Example 1> Electron microscope analysis Ion beam scanning electron microscope (FIB-SEM, [FC-FI20]-FIB II instrument) photographs of the silicon composite (B1) and silicon-carbon composite (C1) prepared in Example 1 are shown in FIG. 2 and FIG. 3, respectively.

[0328] 2 and 3 respectively represent photographs of a silicon composite (B1) and a silicon-carbon composite (C1) analyzed by ion beam scanning electron microscopy (FIB-SEM) at a magnification of 30,000 times.

[0329] Moreover, an ion beam transmission electron microscope (TEM-FIB) photograph of the silicon-carbon composite (1) prepared in Example 1 is shown in Figure 4. Here, the bright white dots represent Si crystals, and the dark dots represent carbon (C). As can be seen from Figure 4, the surface of the silicon-carbon composite (C1) particles contained a large amount of carbon, and the inside of the particles contained a large amount of Si components.

[0330] <Test Example 2> X-ray diffraction analysis The crystal structure of the silicon-carbon composite prepared in the examples was analyzed using an X-ray diffraction analyzer (X'Pert3 from Malvern Panalytical).

[0331] Specifically, the applied voltage was 40 kV and the applied current was 40 mA. The 2θ range was from 10° to 80°, and measurements were performed by scanning at 0.05° intervals.

[0332] 5 and 7 show the results of X-ray diffraction analysis of the silicon-carbon composites of Examples 1 and 4, respectively.

[0333] Referring to FIG. 5 and FIG. 7, as can be seen from the X-ray diffraction patterns, the silicon-carbon composites of Example 1 and Example 4 have peaks corresponding to Si crystals at diffraction angles (2θ) of about 28.3°, 47.5°, 56.1°, 69.1°, and 76.5°, which indicate that they contain crystalline Si, and peaks corresponding to silicon dioxide (SiO x , 0.4≦x≦2). The diffraction angle (2θ) of carbon could not be confirmed because it overlapped with the Si(111) peak.

[0334] <Test Example 3> Analysis of the content of each component element in silicon composite or silicon-carbon composite The contents of the component elements oxygen (O) and carbon (C) in the silicon composites and porous silicon-carbon composites prepared in the examples and comparative examples were analyzed.

[0335] The oxygen (O) and carbon (C) contents were analyzed by an elemental analyzer. The silicon (Si) content was calculated based on the oxygen (O) content.

[0336] <Test Example 4> Measurement of average particle size of silicon composite or silicon-carbon composite The average particle size (D 50 ) to the average diameter D 50 That is, the particle size or median diameter was measured when the cumulative volume reached 50% in particle size distribution measurement by laser beam diffraction method.

[0337] <Test Example 5> Raman Spectroscopic Analysis The silicon-carbon composite prepared in Example 1 was subjected to Raman spectroscopy. The Raman analysis was performed using a micro-Raman analyzer (Renishaw, RM1000-In Via) at 2.41 eV (514 nm). The results are shown in FIG.

[0338] Referring to FIG. 6, the Raman spectrum obtained by Raman spectroscopy shows the G band (1,580 cm -1 ) and D band (1,350 cm -1 ) was observed, which confirmed that the silicon-carbon composite prepared in Example 1 contained electrically conductive carbon.

[0339] Therefore, the silicon-carbon composite prepared in Example 1 has excellent electrical conductivity and can significantly improve the performance of lithium secondary batteries.

[0340] <Test Example 6> Measurement of electrode expansion rate Before the production of an electrode, the thickness (N1) of a rolled negative electrode using the negative electrode active material prepared in the example was measured.

[0341] The cycle life of a secondary battery (coin cell) manufactured using the negative electrode was measured, and the measurement was terminated at 80% of the cycle life. The coin cell was then disassembled, the negative electrode was separated, and it was immersed in a dimethyl carbonate (DMC) solvent and then removed. Next, after the solvent was completely dried, the thickness (N2) of the side of the separated negative electrode was measured using a SEM.

[0342] The ratio of the thickness (N1) of the rolled negative electrode before electrode production to the thickness (N2) of the negative electrode whose measurement was completed at 80% of the cycle life was converted into a percentage and calculated as follows:

[0343] [Formula A] Electrode expansion rate (%) = thickness of negative electrode when measurement was completed at 80% of cycle life (N2) / thickness of rolled negative electrode before electrode production (N1) × 100.

[0344] <Test Example 7> Measurement of capacity, initial efficiency and capacity retention rate of lithium secondary battery The coin cells (lithium secondary batteries) prepared in the examples and comparative examples were each charged at a constant current of 0.1 C until the voltage reached 0.005 V, and then charged at a constant voltage until the current reached 0.005 C. Thereafter, the cells were discharged at a constant current of 0.1 C until the voltage reached 1.5 V, and the charge capacity (mAh / g), discharge capacity (mAh / g), and initial efficiency (%) were measured.

[0345] [Equation 5] Initial efficiency (%) = discharge capacity / charge capacity x 100

[0346] In addition, the coin cells prepared in the examples and comparative examples were each charged and discharged once in the same manner as above, and from the second cycle, they were charged at a constant current of 0.1 C until the voltage reached 0.005 V, at a constant voltage until the current reached 0.005 C, and at a constant current until the voltage reached 0.005 V. Next, they were discharged at a constant current of 0.2 C until the voltage reached 1.5 V, and the cycle characteristics (capacity retention rate, %) at 50 cycles and 100 cycles were measured.

[0347] [Equation 6] Capacity retention rate at 50 cycles (%) = 51st discharge capacity / 2nd discharge capacity × 100

[0348] [Equation 7] Capacity retention rate at 100 cycles (%) = 101st discharge capacity / 2nd discharge capacity x 100

[0349] The element contents and physical properties of the silicon-based raw material powders, silicon composites, and silicon-carbon composites of the examples and comparative examples are summarized in the following Tables 1 to 4. The characteristics of the lithium secondary batteries using them are summarized in the following Tables 3 and 4.

[0350] [Table 1]

[0351] [Table 2]

[0352] [Table 3]

[0353] [Table 4]

[0354] As can be seen from Tables 3 and 4 above, in the silicon-carbon composites of Examples 1 to 9 of the present invention, the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms satisfied a specific range. Therefore, the lithium secondary batteries produced using these exhibited significantly improved performance in terms of discharge capacity, initial efficiency, and capacity retention rate, compared with the lithium secondary batteries of Comparative Examples 1 to 4.

[0355] Specifically, the lithium secondary batteries of Examples 1 to 7, which used silicon-carbon composites with a molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms of 0.03 to 0.44, had discharge capacities of 1,621 mAh / g to 1,923 mAh / g, initial efficiencies of 83.6% to 92.5%, and in most cases, capacity retention rates of 85% or more, demonstrating that the performance of these lithium secondary batteries was excellent overall.

[0356] On the other hand, when comparing the lithium secondary battery of Comparative Example 1 in which etching was not performed in the process of Example 1, the secondary battery of Example 1 had a discharge capacity of 1,849 mAh / g, an initial efficiency of 84.8%, and a capacity retention rate of 85.3%, whereas the lithium secondary battery of Comparative Example 1 had a discharge capacity of 1,542 mAh / g and an initial efficiency of 74.8%, indicating that the discharge capacity and initial efficiency of the latter were significantly reduced compared to the former of Example 1. This is understood to be a result of the fact that in the lithium secondary battery of Comparative Example 1, etching was not performed in the preparation of the silicon-carbon composite, so that an excessive amount of the irreversible material SiO2 remained.

[0357] In addition, when comparing the secondary battery of Example 1, in which the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms was 0.44, with the secondary batteries of Comparative Examples 2 to 4, in which the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms was 0.48 to 0.76, the secondary battery of Example 1 had an initial efficiency of 84.8% and a capacity retention rate of 85.3%, whereas the lithium secondary batteries of Comparative Examples 2 to 4 had an initial efficiency of 79.8% or less and a capacity retention rate of 78 or less, showing performance significantly reduced compared to the lithium secondary battery of Example 1. In addition, the discharge capacity of the lithium secondary battery of Comparative Example 4 was 1,553 mAh / g, which was significantly reduced compared to the lithium secondary batteries of the Examples.

[0358] In particular, in the silicon-carbon composites of Comparative Examples 2 to 4, many pores remained in the composite even after the carbon layer was formed, which increased the BET of the composite and caused some side reactions with the electrolyte, resulting in a decrease in the capacity retention rate of the lithium secondary batteries compared to the lithium secondary batteries of the Examples.

[0359] Furthermore, when the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) was less than 0.01, it was difficult to prepare a silicon-carbon composite.

[0360] On the other hand, in Table 4 above, the silicon-carbon composites (2) of Examples 8 and 9 each including two carbon layers including a first carbon layer and a second carbon layer were composites in which a second carbon layer was formed by spray drying on the first carbon layer of the silicon-carbon composites of Examples 2 and 4, respectively. Since a double carbon layer was formed, the strength of the shell layer was further increased, and the bond (adhesion) between the silicon-carbon composite and the binder was increased, thereby reducing the electrode expansion rate. As a result, the capacity retention rate of the lithium secondary battery after 100 cycles was improved.

[0361] Therefore, by controlling the molar ratio of oxygen (O) atoms to silicon (Si) atoms (O / Si) in the silicon-carbon composite, the performance of lithium secondary batteries can be uniformly improved. Furthermore, by changing the shell structure of the silicon-carbon composite, the characteristics of the secondary battery can be controlled. [Explanation of symbols]

[0362] 10 Pores (voids) 20 Silicon Particles 40 Carbon layer (first carbon layer) 45 Carbon 50 Carbon layer (second carbon layer) (1)Chemical pyrolysis deposition method (2) Liquid coating method

Claims

1. A silicon-carbon composite comprising silicon particles and carbon, wherein the molar ratio (O / Si) of oxygen (O) atoms to silicon (Si) atoms in the silicon-carbon composite is 0.01 to 0.

45.

2. 10. The silicon-carbon composite of claim 1 having a core-shell structure, said core comprising silicon particles and carbon, and said shell comprising a carbon layer.

3. 2. The silicon-carbon composite according to claim 1, wherein the silicon-carbon composite contains pores therein, and the porosity of the silicon-carbon composite is 10% or less.

4. 3. The silicon-carbon composite of claim 2, wherein the shell comprises a first carbon layer comprising at least one selected from the group consisting of amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor deposited graphene, reduced graphene oxide, and carbon nanotubes.

5. the shell comprises two or more carbon layers including a first carbon layer and a second carbon layer; The first carbon layer includes at least one selected from the group consisting of amorphous carbon, crystalline carbon, carbon nanofibers, chemical vapor deposition graphene, and carbon nanotubes; The silicon-carbon composite of claim 2 , wherein the second carbon layer comprises reduced graphene oxide.

6. 2. The silicon-carbon composite of claim 1, wherein the oxygen (O) content in the silicon-carbon composite is 0.5% to 10% by weight, the silicon (Si) content is 38% to 80% by weight, and the carbon (C) content is 18% to 60% by weight, based on the total weight of the silicon-carbon composite.

7. 3. The silicon-carbon composite of claim 2, wherein the carbon (C) content within the core of the silicon-carbon composite is 16% to 45% by weight, based on the total weight of the silicon-carbon composite.

8. 6. The silicon-carbon composite of claim 5, wherein the content of oxygen (O) in the reduced graphene oxide in the second carbon layer is 0.5 wt % to 10 wt %, based on the total weight of the reduced graphene oxide.

9. In the Raman spectrum obtained by Raman spectroscopy of the silicon-carbon composite, -1 ~2,760cm -1 The intensity of the 2D band peak appearing in the range of 1,500 cm is defined as I2D. -1 ~1,660cm -1 The intensity of the G band peak appearing in the range of 1,280 cm -1 ~1,400cm -1 When the intensity of the D band peak appearing in the range is ID, the following Relation 4: [Relationship 4] 0.5<(I2D+IG) / ID≦2.0 The silicon-carbon composite of claim 5 , wherein

10. The silicon-carbon composite is silicon oxide (SiO x , 0.4≦x≦2).

11. A first step of etching a silicon-based raw material powder using an etching solution containing a fluorine (F) atom-containing compound; A second step of filtering and drying the product obtained by the etching to prepare a silicon composite; and A third step of obtaining a silicon-carbon composite by coating the inside of the silicon composite with carbon or by coating the inside of the silicon composite with carbon and forming a carbon layer on the surface of the silicon composite using a chemical pyrolysis deposition method.

2. A method for preparing the silicon-carbon composite of claim 1, comprising:

12. The third step is a process for producing a compound represented by the following formulas 1 to 3: [Formula 1] C N H (2N+2-A) [OH] A (In formula 1, N is an integer from 1 to 20, and A is 0 or 1.) [Formula 2] C N H (2N-B) (In formula 2, N is an integer from 2 to 6, and B is an integer from 0 to 2.) [Formula 3] C x H y O z (In formula 3, x is an integer from 1 to 20, y is an integer from 0 to 25, and z is an integer from 0 to 5.) and conducting the reaction in a gaseous state at 400° C. to 1,200° C., thereby forming carbon in the core and the first carbon layer in the shell.

13. 13. The method for preparing a silicon-carbon composite according to claim 12, further comprising a fourth step of, after forming the first carbon layer, forming a second carbon layer on the first carbon layer by using a liquid coating method.

14. A negative electrode active material comprising the silicon-carbon composite of claim 1.

15. A lithium secondary battery comprising the negative electrode active material of claim 14.

Citation Information

Patent Citations

  • Negative electode active material, its manufacturing method, and negative electrode and lithium battery adopting it

    JP2008198610A

  • Negative electrode active material for lithium secondary battery and its manufacturing method

    JP2018523898A

  • Carbon-coated silicon oxide / graphite composite particles, manufacturing method, and uses thereof

    JP2020527283A

  • Negative active material for rechargeable lithium battery, method of preparing the same, and negative electrode and rechargeable lithium battery including the same

    KR101396521B1

  • Porous silicon-based negative electrode active material and lithium secondary battery containing the same

    JP2016502253A